Culture of entrepreneurship and business management in an Association of Artisans, Catacaos,Perú 2024 - Agurto Ruiz, Karla Paola (2024)
The main objective of the research was to determine the relationship between the culture of entrepreneurship and business management in an Association of Artisans, seeking to contribute to Sustainable Development Goal 8: Decent work and economic growth. An applied methodology with a quantitative approach and non-experimental design was used. The technique used was a survey and the instrument was a questionnaire. The most significant results revealed a moderate direct linear correlation between entrepreneurial culture and business management (Spearman's coefficient: 0.680, p-value: 0.000). Significant correlations were also found between the dimensions of entrepreneurial culture (entrepreneurship, risk consideration, creativity and innovation, value generation, proactivity and information seeking) and entrepreneurial management, with Spearman coefficients ranging from 0.627 to 0.692. These findings highlight the importance of fostering a strong entrepreneurial culture to improve business management in the artisans' association and contribute to local economic development.